Skor Pediatric Risk of Mortality III (Prism III) Sebagai Prediktor Mortalitas Pasien di Ruang Rawat Intensif Anak RSUD Dr. Moewardi Surakarta - Dewi, Mayasari (Jurnal Kedokteran Indonesia, 2009)
Background: Mortality can be predicted from a score system for patient in pediatric intensive care unit. The score system in each intensive care unit is different. It depends on human resources andfacilities. PRISM III score is the most common score system. The objective of this study is to predict patientâs mortality in pediatric intensive care unit using PRISM III and to obtain the best PRISM III cut off point.Methods: A cohort study was conducted in pediatric intensive care unit Dr. Moewardi Hospital Surakarta from August 2008 â February 2009 with 80 samples. In the first 24 hours all of the patients had 17 examinations from PRISM III score. The patients received standard treatment, then was followed until they was discharged from pediatric intensive care unit (death/alive).Results: The results showed that surgery cases were about 57.5% and non surgery cases were 42.5%. The best cut off point PRISM III score was 8. Cox regression analysis demonstrated that patients with PRISM III score 8 had 3.5 mortality risk than PRISM III score < 8. Survival rate patients with PRISM III score 8 was lower than PRISM III score < 8.Conclusion: PRISM III score can be used as a predictor of mortality for patient in pediatric intensive care unit Dr. Moewardi Hospital Surakarta and the best cut-off point PRISM III is 8. Jurnal Kedokteran Indonesia: 1 (1): 40-48Keywords: pediatric intensive care unit, PRISM III, mortality